Virtual Reality with Virtual Private Assistant Research: A Case on Amazon Sumerian (International Journal of Engineering and Computer Science, 2021)
In modern years, there is a growing recognition of Virtual Reality(VR) in education andthe logic behind this may be the distribution programs in various walks of life. With theminimal device framework, the developers can easily construct and organize applicationsthat can be reachable from anywhere without the in-depth understanding of editing andmanaging 3D objects. In an intended design, Intelligent Virtual Assistant offers theopportunity for hospitality services to enhance the customer experience. The VirtualAssistant can give guests a more personalized experience with either a touch or a VirtualAgent, a custom kiosk, or a smartphone. If you are visiting for the first time and need toidentify the local business and location on the map, this MIET Virtual Assistant will helpyou find them. This paper outlines the results of a project undertaken by the Meerut Instituteof Engineering and Technology, AKTU, India, which aims to provide a purposeful hostingservice in the VR area using amazon service which is known as AWS Sumerian . Thisproject’s benefaction and shortcomings are explored.